Evolution of employee opinion in a crowdsourcing logistics company: a catastrophe-embedded RA model. (April 2022) - Song, Yi; Hu, Bin; Xue, Heqiang
Crowdsourcing logistics is a business model for the modern logistics industry. However, the employee behavior of crowdsourcing logistics remains unstable due to the dynamic nature of crowdsourcing logistics. With a small change in environmental factors, e.g., the delivery price, employee opinion may show frequent polarization or reversal that can lead to employee turnover. To explore the mechanism of sudden change in employee opinion and turnover, a cusp catastrophe model is embedded into the relative agreement (RA) model of opinion dynamics to form a catastrophe-embedded RA model. Text data about employee opinion of the crowdsourcing logistics company DaDa are collected for modeling and validation of the catastrophe-embedded RA model. Simulation experiments explore the impact of network structure and delivery price on employee opinion evolution and employee turnover. The catastrophe theory–embedded RA model extends the application of the RA model in the field of opinion dynamics with frequent polarization or reversal.